Peran Transformational Leadership terhadap Kinerja Karyawan di Industri Kimia: Analisis Mediasi Leader-Member Exchange, Knowledge Sharing, dan Innovative Work Behavior - Wishnumurti, Aditya; Firdian, Danil; Marcel, Tjen; Maharani, Anita (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines how transformational leadership influences employee performance through leader-member exchange, knowledge sharing, and innovative work behavior in Indonesia’s chemical industry. Using a quantitative approach, data from 142 employees were analyzed with PLS-SEM. The results show that transformational leadership significantly affects leader-member exchange and knowledge sharing but has no significant effect on task performance or innovative work behavior. Knowledge sharing consistently improves task performance and reduces counterproductive work behavior, while leader-member exchange helps suppress counterproductive behavior. These findings imply that organizations should strengthen work relationships and knowledge-sharing practices to enhance employee performance effectively. Keywords: Transformational Leadership; Leader-Member Exchange; Knowledge Sharing; Innovative Work Behavior; Employee Performance; Counterproductive Work Behavior; Chemical Industry